The Anticancer Effects of the Pro-Apoptotic Benzofuran-Isatin Conjugate (5a) Are Associated With p53 Upregulation and Enhancement of Conventional Chemotherapeutic Drug Efficiency in Colorectal Cancer Cell Lines - Vaali-Mohammed, Mansoor-Ali; Abdulla, Maha-Hamadien; Matou-Nasri, Sabine; Eldehna, Wagdy M.; Meeramaideen, M.; Elkaeed, Eslam B.; El-Watidy, Mohammed; Alhassan, Noura S.; Alkhaya, Khayal; Al Obeed, Omar (Frontiers in Pharmacology, 2022)
The present study aimed to investigate in depth a cytotoxic novel benzofuran-isatin conjugate (5a) with promising potential anticancer activities in colorectal adenocarcinoma HT29 and metastatic colorectal cancer (CRC) SW620 cell lines. Thus, the main cell events involved in tumorigenicity, tumor development, metastasis, and chemotherapy response were explored. Both CRC cell lines were exposed to different concentrations of the compound 5a then subjected to real-time cell viability, migration, and invasion assays, colony formation and cytotoxicity assays, and to flow cytometry for cell cycle analysis and apoptosis determination. Western blot and RT-qPCR were performed to assess the protein and transcript expression levels of epithelial-mesenchymal transition (EMT), cell cycle, and apoptosis markers. We showed that the compound 5a treatment exhibited anticancer effects through inhibition of HT29 and SW620 cell viability, migration, and invasion, in a dose-dependent manner, which were associated with the upregulation of the tumor suppressor p53. The compound 5a also inhibited the colony formation ability of both HT29 and SW620 cells and reversed EMT markers E-cadherin and N-cadherin expression. CRC cell exposure to the compound 5a resulted in a cell cycle arrest at the G1/G0 phase in HT29 cells and at the G2/M phase in SW620 cells, along with the downregulation of cyclin A1 expression, described to be involved in the S phase entry. Furthermore, the compound 5a-induced apoptosis was associated with the downregulation of the anti-apoptotic Bcl-xl marker, upregulation of pro-apoptotic Bax and cytochrome c markers and increased mitochondrial outer-membrane permeability, suggesting the involvement of mitochondria-dependent apoptosis pathway. In addition, the combination studies of the compound 5a with the main conventional chemotherapeutic drugs 5-Fluorouracil, Irinotecan and Oxaliplatin, showed more potent cytotoxic effect in both CRC cells than single treatment. In conclusion, our findings described the interesting in vitro anticancer properties of the compound 5a shown to have possible antitumor, antimetastatic, and pro-apoptotic activities, with enhancement of the cytotoxic efficiency of conventional chemotherapeutic drugs. In vivo studies are requested to confirm the promising anticancer potential of the compound 5a for CRC therapy.